Clinical and psychometric validation of a questionnaire module, the EORTC QLQ-STO 22, to assess quality of life in patients with gastric cancer - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The purpose of this study was to define the measurement properties and clinical validity of the European Organisation for Research and Treatment of Cancer (EORTC) questionnaire module to assess health-related quality of life (HRQL) in gastric cancer. The EORTC gastric cancer module, QLQ-STO 22, was administered with the QLQ-C30, core questionnaire, to 219 patients undergoing treatment with curative or palliative intent before and after treatment. Reliability and validity of the module was tested and patients' debriefing comments analysed. Compliance rates were high, questionnaires well accepted and less than 4% of items had missing data. Multi-trait scaling analyses and face validity refined the module to five scales and four single items. Scales distinguished between clinically distinct groups of patients and demonstrated treatment-induced changes over time. Test-retest scores demonstrated good reliability. The EORTC QLQ-STO 22 demonstrates psychometric and clinical validity that supports its use to supplement the EORTC QLQ-C30 to assess quality of life in patients with gastric cancer undergoing surgery, surgery and chemoradiotherapy, palliative chemotherapy, palliative surgery and best supportive care. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: quality of life; gastric cancer; questionnaires; QLQ-STO 22; QLQ-C30; psychometrics; ADVANCED ESOPHAGOGASTRIC CANCER; RANDOMIZED-TRIAL; SURGICAL-TREATMENT; FLUOROURACIL; CARCINOMA; EPIRUBICIN; CISPLATIN; SURVIVAL; GASTRECTOMY; MORTALITY